Temporal and geographical prevalence of carbapenem-resistant Pseudomonas aeruginosa and the in vitro activity of ceftolozane/tazobactam and comparators in Taiwan—SMART 2012–2021 - James A. Karlowsky; Mark G. Wise; Tai-Chin Hsieh; Hung-Chi Lu; Wei-Ting Chen; Ming-Huei Cheng; Fakhar Siddiqui; Katherine Young; Mary R. Motyl; Daniel F. Sahm (Journal of Global Antimicrobial Resistance, 2023)
ABSTRACT: Objectives: To determine the in vitro activities of ceftolozane/tazobactam (C/T) and comparators against Pseudomonas aeruginosa isolates cultured from hospitalised patient samples in Taiwan from 2012 to 2021 with an additional focus on the temporal and geographical prevalence of carbapenem-resistant P. aeruginosa (CRPA). Methods: P. aeruginosa isolates (n = 3013) were collected annually by clinical laboratories in northern (two medical centres), central (three medical centres), and southern Taiwan (four medical centres) as part of the SMART global surveillance program. MICs were determined by CLSI broth microdilution and interpreted using 2022 CLSI breakpoints. Molecular β-lactamase gene identification was performed on selected non-susceptible isolate subsets in 2015 and later. Results: Overall, 520 (17.3%) CRPA isolates were identified. The prevalence of CRPA increased from 11.5%–12.3% (2012–2015) to 19.4%–22.8% (2018–2021) (P ≤ 0.0001). Medical centres in northern Taiwan reported the highest percentages of CRPA. C/T, first tested in the SMART program in 2016, was highly active against all P. aeruginosa (97% susceptible), with annual susceptibility rates ranging from 94% (2017) to 99% (2020). Against CRPA, C/T inhibited >90% of isolates each year, with the exception of 2017 (79.4% susceptible). Most CRPA isolates (83%) were molecularly characterised, and only 2.1% (9/433) carried a carbapenemase (most commonly, VIM); all nine carbapenemase-positive isolates were from northern and central Taiwan. Conclusion: The prevalence of CRPA increased significantly in Taiwan from 2012 to 2021 and warrants continued monitoring. In 2021, 97% of all P. aeruginosa and 92% of CRPA in Taiwan were C/T susceptible. Routine in vitro susceptibility testing of clinical isolates of P. aeruginosa against C/T, and other newer β-lactam/β-lactamase inhibitor combinations, appears prudent.